2020
DOI: 10.1177/1352458520937385
|View full text |Cite
|
Sign up to set email alerts
|

A validation study for remote testing of cognitive function in multiple sclerosis

Abstract: Objectives: Determine the validity and reliability of a remote, technician-guided cognitive assessment for multiple sclerosis (MS), incorporating the Symbol Digit Modalities Test (SDMT) and the California Verbal Learning Test, Second Edition (CVLT-II). Methods: In 100 patients, we compared conventional in-person testing to remote, web-assisted assessments, and in 36 patients, we assessed test–retest reliability using two equivalent, alternative forms. Results: In-person and remote-administered SDMT ( r = 0.85)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
5
16
0
1
Order By: Relevance
“…In conclusion, the present study shows that in-home TNP testing is a valid and clinically useful approach for obtaining a limited neuropsychological profile, and that the findings extend the limited data that have been reported by other groups to date ( Barcellos et al., 2020 ). These findings show that a cognitive test battery including tests of attention, processing speed, language, visuospatial processing, and memory can be administered using in-home TNP testing.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In conclusion, the present study shows that in-home TNP testing is a valid and clinically useful approach for obtaining a limited neuropsychological profile, and that the findings extend the limited data that have been reported by other groups to date ( Barcellos et al., 2020 ). These findings show that a cognitive test battery including tests of attention, processing speed, language, visuospatial processing, and memory can be administered using in-home TNP testing.…”
Section: Discussionsupporting
confidence: 87%
“…Although these results are promising, it is notable that the TNP testing in all studies included in the meta-analysis involved patients or participants undergoing TNP testing in either a controlled clinic or laboratory setting. A recent study from Barcellos and colleagues (2020 ) involved in-home TNP testing with patients with multiple sclerosis. The authors’ analyses showed that tests of verbal memory and processing speed could be administered remotely to patients in their homes.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective observation of the tasks administered remotely during fully or partially remote assessments begun during the lockdown reveals that many were verbal in nature, in accordance with previous literature [ 17 , 24 , 30 ]. These included, for example, the Rey Auditory Verbal Learning Test (RAVLT, [ 37 ]), story recall [ 38 ], verbal fluency, reading, sentence completion, and several verbal intelligence subtests from the Wechsler Adult Intelligence Scale (WAIS [ 39 ];).…”
Section: Case Illustration: Response Of An Israeli Assessment and Rehabilitation Organizationsupporting
confidence: 85%
“…They found that verbally administered tests, including list learning, digit span, and verbal fluency tasks, were generally not affected by administration method, while remote versions of visual and motor tests like picture naming and clock drawing received less support. More recently, Barcellos et al [ 30 ] reported further evidence that tests of verbal memory and processing speed could be effectively administered remotely.…”
Section: Remote Testing During Covid-19: Recommendations and Considerationsmentioning
confidence: 99%
“…In an analysis of 8022 follow-up visits from 4199 patients in which the MSPT was integrated into visits, the tablet-based data collection resulted in more patients completing assessment and in a shorter time frame relative to analog methods, making it easier to incorporate these tests into care in spite of time constraints placed on HCPs [ 115 ]. Digitally administered tools also hold promise for use via telehealth, which has become important during the COVID-19 pandemic; early work seeking to validate remote use of the Symbol Digit Modalities Test (SDMT) and California Verbal Learning Test (CVLT-II) suggests that these tools may be effectively used remotely [ 116 ]. Such self-administered and/or remote technology-based screening tools are likely the future of invisible symptom monitoring, as they can help to streamline information collection, thus allowing more concerns to be addressed in a shorter amount of time during clinical visits.…”
Section: How Can We As a Community Address Invisible Symptoms In A Comprehensive Manner?mentioning
confidence: 99%